The Activity Of Pregnant Women In The Pregnancy Class Reviewed From The Support Of Husband In Singogalih Village Tarik Sidoarjo District In 2020 - Vidia Atika Manggiasih; Anita Tripsilowati (Universitas STRADA Indonesia, 2023)
One of the causes of the inactivity of mothers to join the class of pregnant women is due to work, limited time, opportunities, education, knowledge, lack of self-motivation and lack of support from the husband. Preliminary survey results conducted in Singogalih Village, Tarik Sidoarjo District in January 2020, were obtained from 10 participants who were enrolled in the pregnant mother’s class, only 4 pregnant women had attended the pregnant mother’s class. This shows that there are still many pregnant women who have not yet joined the class of pregnant women. The design of this research is correlation analytic with cross sectional approach. The population studied was all pregnant women with samples of second and third trimester pregnant women of 20 pregnant women. The independent variable was examined by the husband's support while the dependent variable was activeness in taking the class of pregnant women. The sampling technique uses non-probability sampling technique by means of purposive sampling, which is taking samples in accordance with the wishes of researchers. The results were analyzed using the Spearman Rank statistical test. The results obtained by the significance value (α) is 0.05 with a correlation coefficient of 0.039 that the majority of respondents (65%) actively attend the class of pregnant women as many as 13 out of 20 pregnant women. Then the conclusion is that Ho is rejected and H1 is accepted, meaning that there is active activity of pregnant women in the pregnant class in terms of the husband's support about the pregnant class in Singogalih village, Tarik Sidoarjo district in 2020. Based on the results of research that the husband's support in the form of physical and psychological comfort obtained through knowledge that pregnant women need to be cared for, loved, and loved. If the pregnancy is accompanied by full support from her husband and family, then the pregnancy process will go well which will indirectly affect the health of the mother and the fetus she is carrying.